A complex craniovertebral junction malformation in a patient with late onset glycogenosis 2 - Cotelli, Mariasofia (Medknow Publications & Media Pvt Ltd, 2014)
Glycogenosis II (GSDII) is an autosomal recessive lysosomal storage disorder resulting from deficiency of acid alpha-glucosidase and subsequent lysosomal accumulation of glycogen in skeletal, cardiac and smooth muscles. The late-onset form is characterized by wide variability of the phenotypical spectrum. Clinical findings may include muscle weakness, respiratory insufficiency, vascular abnormalities, low bone mineral density and higher risk of developing osteoporosis. Craniovertebral junction (CVJ) malformations have never been described so far. We here report on a GSDII 43-year-old woman who harbored the mutations IVS1-13T>G and c.2237G>A in the acid alpha-glucosidase gene. She recurrently suffered from headache, neck pain and dizziness. Brain MRI and CT scan showed the presence of a very rare complex CVJ malformation composed of basilar invagination, basiocciput hypoplasia, partial C1 assimilation, C1 posterior arch aplasia and C1 lateral mass hypoplasia and offset. Although we cannot rule out their coincidental occurrence, the rarity of multiple CVJ malformations in the general population as well as the well-known GSDII multisystem involvement should suggest to study the CVJ in the diagnostic process of GSDII patients in order to assess the CVJ malformation frequency in GSDII population and verify a possible relationship between these two conditions.